Role of Regular Physical Exercise in Tumor Vasculature: Favorable Modulator of Tumor Milieu - Esteves, Mário; Monteiro, Mariana P.; Duarte, Jose Alberto (International Journal of Sports Medicine, 2020)
The tumor vessel network has been investigated as a precursor of an inhospitable tumor microenvironment, including its repercussions in tumor perfusion, oxygenation, interstitial fluid pressure, pH, and immune response. Dysfunctional tumor vasculature leads to the extravasation of blood to the interstitial space, hindering proper perfusion and causing interstitial hypertension. Consequently, the inadequate delivery of oxygen and clearance of by-products of metabolism promote the development of intratumoral hypoxia and acidification, hampering the action of immune cells and resulting in more aggressive tumors. Thus, pharmacological strategies targeting tumor vasculature were developed, but the overall outcome was not satisfactory due to its transient nature and the higher risk of hypoxia and metastasis. Therefore, physical exercise emerged as a potential favorable modulator of tumor vasculature, improving intratumoral vascularization and perfusion. Indeed, it seems that regular exercise practice is associated with lasting tumor vascular maturity, reduced vascular resistance, and increased vascular conductance. Higher vascular conductance reduces intratumoral hypoxia and increases the accessibility of circulating immune cells to the tumor milieu, inhibiting tumor development and improving cancer treatment. The present paper describes the implications of abnormal vasculature on the tumor microenvironment and the underlying mechanisms promoted by regular physical exercise for the re-establishment of more physiological tumor vasculature.
Keywords: vascularization; perfusion; exercise training; cancer; metastasis